Metáfora na terminologia do petróleo no espaço da Comunidade de Países de Língua Portuguesa (CPLP): Angola, Brasil e Portugal - Silveira, Theciana Silva (Universidade Federal de São Carlos, 2021)
Metaphors, a topic that arouses great interest among scholars, have been approached from different perspectives. Seen as a cognitive resource of language, it is now understood as a fundamental mechanism for understanding several human experiences and it is present in everyday life, no longer seen only as a stylistic mechanism of language, restricted to rhetoric and literature. Thus, metaphor, as a productive naming strategy, is also relevant for the analysis of the object of linguistic-based descriptive terminological studies. In this sense, the present thesis has as main objective to analyze the linguistic metaphors present in the petroleum universe within the Community of Portuguese Language Countries (CPLP), especially in Angola, Brazil and Portugal. The objective was also to identify the conceptual and denominational differences that exist among the varieties of Portuguese in the member States included in this research and to propose a classification of the metaphorical models of petroleum terminology. The Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (1980) and, in the scope of Terminology, the Sociocognitive Terminology Theory (STT) by Temmerman (2000) are taken as the theoretical basis of this study.With regard to methodological aspects, the only terminological work in Portuguese on petroleum was considered as a data source, covering the three varieties of Portuguese from the aforementioned countries. The dictionary in question, which was called lexicographical corpus, is monolingual with English equivalences. As it is a printed work, it was necessary to digitize it and treat it computationally, so that it was possible to manipulate such a large volume of data. The analyses were divided into two parts: (1) domain metaphors, in which it was sought to demonstrate the motivations of the metaphor, with which areas of domain these metaphors are related; and (2) cultural metaphors, in which it was sought to identify the influences of cultural differences in the conceptualization and denomination of concepts in petroleum terminology by professionals in those countries. Regarding the results of the analyses of part (1), four aspects were observed: (i) metaphors of perception of similarities between scientific and non-scientific domains; (ii) ontological metaphors of personification; (iii) metaphors motivated by domains of metaphorical nuclei of human-world relations; and (iv) metaphors of visual domains; as can be seen in the terms canhão de ar, óleo morto, poço mãe e linha de matar, belonging to each aspect, respectively. Regarding the results of the analyses of part (2), 10 sets were presented that contrast the three varieties of Portuguese investigated in this thesis. Through the analyses, it was possible to understand that the similarity relations are usually linked to the form and/or function of the referents, hence the importance of mapping similarities between domains to understand how specialized knowledge is structured. It was also observed that, when naming a particular entity, conceptual traits are evidenced, which often differ when related to the different varieties of Portuguese, because, although it is the same language, there is always diversity in the conceptualization of reality.
Metaphor in the oil terminology at the Community of Portuguese Language Countries (CPLP): Angola, Brazil and Portugal
Keywords: Terminologia; Metáfora; Petróleo; Comunidade dos Países de Língua Portuguesa; Terminology; Metaphor; Petroleum; Community of Portuguese Language Countries; LINGUISTICA, LETRAS E ARTES::LINGUISTICA